Effectiveness of NSAIDs in the treatment of major depressive disorder: a comprehensive review - Beatriz dos Santos Caldeira (2020)
Background/Objectives: The inflammatory hypothesis in the aetiology of depression raised the opportunity for new therapeutic tools as first line, adjunctive or symptomatic treatment of Major Depressive Disorder (MDD). Studies assessing the efficacy of nonsteroidal anti-inflammatory drugs (NSAIDs) have yielded inconsistent results. The present review provides an updated overview of such studies with the aim of clarifying the effectiveness of NSAIDs as therapeutic strategies in patients with MDD. Methods: A literature search was conducted to retrieve clinical trials using NSAIDs for the treatment of MDD. Besides the completed randomised and controlled clinical trials (RCTs), non-randomised and non-placebo-controlled trials were also included in the search. Studies with NSAIDs as monotherapy and/or as adjunct of antidepressant therapies, across all age groups were included to tentatively strengthen the qualitative assessment of NSAID effectiveness. Relevant articles, published prior to January 2020 were retrieved by querying eight databases, namely PubMed, Google Scholar, PubMed Central, Web of Science, JAMA Psychiatry, ClinicalTrials.gov, Cochrane Central Register of Controlled Trials and ICTRP. Additional articles were manually scrutinized from bibliography listings of the selected articles. Results: Fourteen records, comprising 15 clinical studies, were identified for inclusion in the qualitative synthesis. Seven RCTs investigated the efficacy of NSAIDs in a total of 2758 patients. Six of these demonstrated a significantly positive effect when used as adjunctive treatment, and one demonstrated no effect as monotherapy. Among the eight remaining non-RCTs studies, five analysed the effect of adjunctive NSAIDs treatment on the depressive symptoms of 130 277 patients, from which two revealed a significantly negative effect and three showed no effect. The other three non-RCTs, conducted on a total of 20 865 non-depressed participants, failed to confirm the preventive effect of NSAIDs. Internal and external validity is compromised by the majority of the study designs. In particular, most RCTs had small sample sizes and short follow-up durations. Additionally, the studies were heterogeneous in terms of exposure and outcome assessments, therapeutic schemes as to drug combinations and dosage, as well as covariates applied for result adjustments. Conclusions: Overall, NSAIDs may exert a beneficial therapeutic effect in MDD as an adjunctive treatment to antidepressants, although methodological heterogeneity introduces some inconsistencies. NSAIDs appear to have no effect as a preventive measure in MDD, particularly amongst the elderly. Study designs need to address the highly heterogeneous pathophysiology and presentation of MDD by deep phenotyping, and by targeting specific inflammatory mechanisms. Selective patient recruitment for uniformity, together with well-matched controls, can provide statistically powerful and clinically meaningful data. Genotypic profiling would ultimately contribute towards a better understanding of the role of inflammation, and anti-inflammatory drugs, in MDD.